WILDLIFE AND TECHNICAL SIGHTS AS THE TOPIC OF THE CROSS-BORDER COOPERATION AND RESEARCH - Petr, MACH (Trends in education, 2015)
The article deals with an international project concerning the issues of the Bavarian border area with respect to wildlife, technology and culture in historical context. The project includes the counties of Tachov, Domazlice and Klatovy on the Czech territory and the counties of Tirschenreuth, Neustadt a.d. Walnaab, Schwandorf, Cham, Regen and Freyung - Grafenau on the Bavarian side of the border. Sumava National Park, Sumava Reserve and Bayerische Wald National Park form a unique UNESCO protected wilderness complex. Particular investigation teams were aimed at the exploration of common features as well as the differences of both cultures present in the border area. Standard research methods were often enhanced by using qualitative methods of oral history. The contribution is mainly aimed at the field of technical sights and the history of crafts.
Keywords: technical sights; Czech - Bavarian border area; history of crafts; oral history.